Do consumers want mobile commerce? A closer look at M-shopping and technology adoption in Malaysia - Ghazali, Ezlika Mohd; Mutum, Dilip S.; Chong, Jiu Hui; Nguyen, Bang (Emerald, 2018)
Purpose: Mobile shopping is expected to emerge as a new way of shopping as the Asia Pacific region moves towards the digital era. It is important to understand factors that influence consumers’ intentions to adopt this new shopping channel, especially in developing countries such as Malaysia where it has the fastest growing mobile penetration rate in the world. The purpose of this paper is to integrate the Technology Acceptance Model (TAM) and the Theory of Planned Behaviour (TPB), and includes additional variables such as personal innovativeness (PI) and trust. Design/methodology/approach: Empirical data from 453 consumers were tested against a proposed model using partial least squares structural equation modelling. Findings: Findings suggest that most of the constructs in the model (i.e. trust, perceived ease of use, perceived usefulness, attitudes, PI and perceived behavioural control) influence a shopper’s intentions towards adopting mobile shopping. For example, consumers’ attitudes towards M-shopping adoption is higher if a system is not complex and easy to use; if consumers can easily pull out their mobile devices from their pockets to browse or shop by using just one finger, without a complicated process, they tend to use M-shopping channels. In addition, when mobile technology is user-friendly and free from mental effort, it creates positive perceptions that the system is useful, developing stronger intentions for consumers to adopt this alternative. Originality/value: Since M-shopping is a personalised activity that involves money transactions, consumers are more cautious with adoption intentions, and do not follow social norms blindly. Thus, the empirical evidence from Malaysian consumers contributes to literature with insights into their specific m-shopping behaviour in this emerging market. In addition, from a theoretical perspective, the research model in this study integrates both TAM and TPB to provide a holistic view of consumers’ M-shopping adoption intentions in an emerging market, incorporating user-centric factors (i.e. trust and PI). An important finding which differs from other studies is that the relationship between subjective norms and behavioural intention to use M-shopping was not significant, which is contrary to the findings of previous studies. Moreover, attitude was found to mediate the effect of PEOU and PU on consumer’s intention towards mobile shopping adoption. The validated instrument would serve as a useful guideline for researchers during development and refinement of studies on M-shopping.